How do capital controls and macroprudential policy interact with monetary policy in a small open economy? - Lim, Hyunkang (2021)
In this paper, I focus on how macroprudential or capital control policy complements monetary policy of small open economies in the face of foreign interest rate shock. I build the base model followed by Aoki et al. (2018) and simulate the impulse response to the foreign interest rate shock and compare the two policies in terms of welfare. The results show that macroeconomic variables under low interest rate environment are more volatile than under high interest rate when the foreign interest rate shock is transmitted to SOEs. It implies that low interest rate environment is more vulnerable to recession than high interest rate environment. I also find that both macroprudential policy and capital control can help to mitigate the influence of foreign interest rate shock but capital control is a better instrument than macroprudential policy in terms of welfare.